Análise multitemporal da morfologia de fundo da Baía de São Marcos – Setor adjacente ao Porto do Itaqui / MA - ARAÚJO JUNIOR, Wilton Pires de (2019)
São Marcos Bay is located in “Golfão Maranhense” and it is a pleistocene estuarine system, that receive hidrosedimentological contribution from Mearim, Pindaré and Grajaú rivers, being strongly influenced by semi-diurnal macrotides. The main objective of this study was to perform a multitemporal analysis (25 years - from 1977 to 2002) of the bathymetry and bottom morphology of this water body in the sector adjacent to Itaqui Port through quantification and estimation of rates of growth / displacement, identification of areas of deposition and erosion and characterization of bedforms. The methodology consisted in the acquisition and georeferencing of bathymetric maps No. 410, issued by the Management Hydrography and Navigation of Navy of Brazil and the digitization of bathymetric isobath and quotas. Bathimetric maps were developed from bathymetric contour (scale 1:135.000), with spacing of 5 meters from the level curves, which allowed, with the bathymetric cross sections, the analysis of multitemporal quantitative dimensions of the bedforms. The results of multitemporal analysis of the bathymetric dynamics showed morphological changes both of order as the depth in the study area, showing the high dynamics in terms of action of macrotides and reverse flows active in the area. Ten morphological features were identified: Main Channel and Itacolomi, Almas, Meio, Complexo do Coral, Darlan, Cerca, Cavalos, Lanzudos and A banks. The sandy banks identified are included in the Perillo´s classification (1995) as elongated bars of tide, with provision for longitudinal flow of tidal currents in reverse, and Bank do Meio and da Cerca may still be classified as marginal linear bar the channels. The banks had orientation and longitudinal displacement and / or growth towards NE, in displacement rates ranging from 2.9 to 8.2 m / year, showing a more pronounced action of the ebb currents in the process of reworking the basic features. However, the Darlan Bank and the lower portion of the longitudinal axis of the Coral do Sul bank, presented movement to SW, which may be associated with the phenomena of resonance and amplification of tide occurring in the region. The fact of the São Marcos Bay is located in the frontal area of the estuary of the Mearim river, means that this bay has a natural tendency to sandy fill, attested in this study.